A Nation on the Line Call Centers as Postcolonial Predicaments in the Philippines - Padios, Jan M. (Duke University Press, 2018)
A NATION ON THE LINE is an ethnographic study of the call center industry in the Philippines and of its workforce composed of young, largely college-educated Filipinos. Padios merges several lines of inquiry about Pacific transnationalism, about the role of affective labor in global markets, and about critique of Filipino exploitation by the United States through economic and military power since independence-- in order to consider how post-colonial and post-industrial changes in the Philippines' role in global capitalism and culture are brought to bear in everyday life. Padios argues that the call center industry serves as a rich case-study for how Filipinos work within hegemonic dynamics of relational service and an understanding of American consumer culture in ways that figure Filipinos' sense of identity and aspirations at the national and individual levels.